The lead and cadmium content in rice and risk to human health in China: A systematic review and meta-analysis - Xianliang Huang; Bo Zhao; Yanlei Wu; Mingtian Tan; Lisha Shen; Guirong Feng; Xiaoshan Yang; Shiqi Chen; Youming Xiong; En Zhang; Hongyu Zhou (PLoS ONE, 2022)
Numerous studies have investigated concentrations of lead (Pb) and cadmium (Cd) in rice in China, but have come to divergent conclusions. Therefore we systematically reviewed and meta-analyzed the available evidence on levels of Pb and Cd in rice in different regions of China in order to assess the potential risk to human health. The meta-analysis included 24 studies of Pb levels and 29 studies of Cd levels, published in 2011–2021. The pooled Pb concentration in rice was 0.10 mg per kg dry weight (95% CI 0.08−0.11), while the pooled Cd concentration was 0.16 mg per kg dry weight (95% CI 0.14−0.18). These levels are within the limits specified by national food safety standards. However, the total target hazard quotient for both metals exceeded 1.0 for adults and children, suggesting that rice consumption poses a health risk.